Continuous-flow protocol for the synthesis of enantiomerically pure intermediates of anti epilepsy and anti tuberculosis active pharmaceutical ingredients. Issue 6 (29th January 2019) - Aguiar, Renata M.; Leão, Raquel A. C.; Mata, Alejandro; Cantillo, David; Kappe, C. Oliver; Miranda, Leandro S. M.; de Souza, Rodrigo O. M. A.
Abstract : Continuous-flow production of chiral intermediates plays an important role in the development of building blocks for Active Pharmaceutical Ingredients (APIs), being α-amino acids and their derivatives widely applied as building blocks. Abstract : Continuous-flow production of chiral intermediates plays an important role in the development of building blocks for Active Pharmaceutical Ingredients (APIs), being α-amino acids and their derivatives widely applied as building blocks. In this work we developed two different strategies for the synthesis of intermediates used on the synthesis of levetiracetam/brivaracetam and ethambutol. The results obtained show that methionine methyl ester can be continuously converted to the desired ethambutol intermediate by RANEY® Nickel dessulfurization/reduction strategy whereas levetiracetam/brivaracetam intermediates could be synthesized by both RANEY® Nickel (without H2 ) and Pd/C–H2 approach or by photochemical desulfurization.